Study of Hepatitis B core Antibody (HBcAb) among Pregnant women and their Newborn at Delivery at Umaru Shehu Ultra-Modern Hospital Maiduguri, Borno State Nigeria - Garba, Jamilu; Oba, Asime; BukBuk, David N.; Ruwa, Abdulhamid Musa; John, Barka; Isah, Hadiza; John, Kwata Veronica; Musa, Jasini Athanda (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Hepatitis B virus infection (HBV) is a worldwide Health problem that has destroyed the lives of people that were predisposed to viral attack, with a significant public implication. The main objectives of this study are to determine the overall prevalence of Hepatitis B Core antibodies in mothers, the overall prevalence of Hepatitis B Core antibodies in their newborns, the prevalence according to the age of mothers, the prevalence according to the gender of the newborns and maternal transfer of HBcAb from the mother to their newborns. A total of 101 plasma were collected from pregnant women and their newborns in the delivery room from the maternity ward at the Umaru Shehu ultra-modern Hospital Maiduguri, Borno state, Nigeria. Pro-med gold Rapid Diagnostic test kits from the United State of America (USA) was used for the detection of Hepatitis B core antibody. Of the 101, mothers and 101 newborns that were assayed for, mothers within the age range of 17 – 40 years with mean ± SD age of 25.9 (±5.2) years, having an overall prevalence of 28.7% for HBcAb of the mothers observed from the result analysis of plasma from pregnant women attending an antenatal program at the Umaru Shehu ultra-modern Hospital Maiduguri, Borno state, Nigeria. Hepatitis B Virus remains a threat to be causing public Health Havoc Globally, this research has revealed that a significant proportion of 72 (71.3%) of the study population is at risk of being infected with HBV since they have no detectable marker of infection or immunity against the virus. Therefore, there is a need for regular and prompt screening of pregnant women for HBV infection and vaccination of those at risk.